A Linguistic Analysis of Mobile Phone Companies’ Slogans: A Case of Vodacom and Tigo in Tanzania - Peter Rabson Mziray; Bazili Evarist Bamuhiga (Journal of Language and Literature, 2021)
This paper presents findings of a Linguistic Analysis of Mobile Phone Companies’ Slogans: a case of Vodacom and Tigo in Tanzania. It specifically aimed at analysing linguistics forms used in constructing mobile phone companies’ slogans and examining the type of illocutionary acts portrayed by the slogans. A total of 25 slogans were collected from online websites of the Tigo and Vodacom mobile phone companies using documentation method and analysed using content analysis. The findings indicate that slogans from mobile phone companies mostly use sentences and, in some instances, phrases and words. Also, the findings revealed that the dominant illocutionary speech acts embedded in the slogans is assertive which intends to change the beliefs of the customer.   The other illocutionary speech acts identified are directive which requires the customers to take action in regard to the services and products advertised; and commissive which shows a promise for better services and products for opting customers. Conclusively, mobile phone companies prefer to use sentences and, in few instances, paired phrases to construct the slogans. The constructed slogans largely portray assertive acts which are complemented by commissive and directive acts. The complementation is what makes mobile phone companies have more than one slogan for communicating a complete intended message.